PENGARUH FIRM SIZE, QUICK RATIO (QR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA) DAN KUPON OBLIGASI TERHADAP HARGA OBLIGASI - Amal, Muhammad Khairul; Siwiyanti, Leonita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the effect firm size, quick ratio (QR), debt to equity ratio(DER), return on assets (ROA) and coupon bond to bond price at corporates listed onIndonesia Bond Pricing Agency (IBPA) on period 2012-2016. The population in thisstudy amounted to 67 companies and obtained a sample of 23 companies. The sampleselection in this study used purposive sampling method and samples are selected basedon predetermined criteria. Data collection method used is documentation method that isby recording or documenting data listed in annual report on (IDX) and bond data onIBPA. Data analysis technique used in this research is panel analysis in Eviews 9.0